The missile crisis from a Cuban perspective - Karlsson, Håkan, 1962- author.
1 online resource
Keywords: "Previous works on the Cuban Missile Crisis (1962) have approached the topic from the point of view of the U.S. and its allies, while Cuban experiences have still not been sufficiently discussed. This book presents new aspects which have seldom - or never - been offered before, giving a detailed account of the crisis from a Cuban perspective. It also investigates the archaeological and anthropological aspects of the crisis, by exploring the tangible and intangible remains that still can be found on the former Soviet missile bases in the Cuban countryside, and through interviews which add a local, human dimension to the subject"--